Clinical presentation, risk factors, complications and outcome of acute myocardial infarction in elderly patients - S., Sandhya; P., Mohanraj (International Journal of Research in Medical Sciences, 2017)
Background: Myocardial Infarction is one of the most common causes of mortality and morbidity among the elderly patients. Also, it is known for wide range of clinical presentations other than chest pain. This article enlightens the clinical features, risk factors, complications, prognosis and outcome of Acute myocardial infarction in elderly patients. The objective of this study was to assess the risk factors, various symptoms, complications, prognosis and outcome of elderly patients with Acute myocardial Infarction (AMI). Methods: This is a prospective study done over a period of two years in a tertiary care hospital in South India. 80 elderly patients who were diagnosed as AMI were included in the study. Results: Among the eighty patients the majority of the patients belonged to the age group 60-69 years. Twenty percent of the patients presented without chest pain. The atypical presentations included dyspnoea, giddiness, vomiting, sweating and epigastric pain. Mortality rate was 20%. Conclusions: This study showed that even though chest pain was the most common presentation in elderly AMI patients, they were also found to have atypical presentations like shortness of breath, giddiness, vomiting, sweating and epigastric pain. This signifies the need of examining physicians to meticulously identify acute myocardial infarction in elderly though they may not present typically.